Biological aspects of the development and self-concept in adolescents living in single-parent families - Veček, Andrea (Array, 2009)
Abstract: In this study we investigate whether there are differences between adolescents who grow up in single-parent families and those who grow up in nucleus families. We have decided that there are no differences in the physical development between the adolescents who are growing up in single parent families and those growing up in nucleus families. There is no difference in the self-concept between these two groups, except in the ethical and moral self-image of adolescents living with one parent. Adolescents living in single-parent families have a weaker moral self-image. It can thus be concluded that physical development and positive self-concept (a favorable image of oneself) in adolescents do not depend on whether an adolescent is growing up in a single-parent or a nucleus family, but on the different characteristics of parents and their relationship with children, whether they are married or not. For the children development the best is healthy marriage of their parents